(untitled) (Research, Society and Development, 2021)
Abortion is a common event that directly affects the family, social and health spheres. It is defined by the World Health Organization (WHO) as the expulsion or extraction of the fetus before 20 weeks or weighing less than 500g and has well-defined clinical and histopathological characteristics, ranging from benign conditions to life-threatening pathologies. Aiming to outline the profile of histopathological findings by uterine curettage for abortion in a maternity hospital in the city of Aracaju, State of Sergipe, between 2015 and 2017, a total of 2473 findings were analyzed. Of these, the majority corresponded to incomplete abortion (98.83%) and to products of conception (61.91%). Seven cases of hydatidiform mole were found – four incomplete and three complete. In the profile of the population studied, 91.14% of women did not have partners and 88.31% were single. The abortion rate per ten thousand inhabitants was also analyzed, drawing attention to the fact that the greater Aracaju concentrates a number about four times greater than other municipalities in the state of Sergipe. There is a lot of debate about the high costs of performing routine uterine curettage with histopathological analysis, since the risk of developing gestational trophoblastic disease is low, corresponding to 0.003% in the present study. Although this is true, when comparing the clinical aspect of the abortion with the histopathological findings, a p of 0.23 was found, and it was not possible to reliably establish a clinical profile for potentially malignant conditions.